Challenges and Opportunities for Sustainability of Human Resource Development in Industry 4.0 - Oluwatoyin, Folashade; Mardikaningsih, Rahayu (Bulletin of Science, Technology and Society, 2024)
This study aims to analyze the challenges and opportunities for sustainability-focused human resource development in the industrial era 4.0. Based on the literature analysis, it was found that the main challenges include the lack of integration of sustainability in training programs, resistance to new technologies, and the lack of synergies between the government, private sector, and educational institutions. In addition, the competency gap between industry needs and workforce skills is also a significant obstacle. However, the industrial era 4.0 also creates strategic opportunities to integrate sustainability through technological innovations such as IoT (Internet of Things) and cyber-physical systems, multi-stakeholder collaboration, and the adoption of green human resource management principles. If taking advantage of these opportunities, organizations can improve workforce competencies while supporting long-term sustainability goals. This study provides important insights for policy makers and organizations to design HR training strategies relevant to the industrial era 4.0.